The Ambivalent Impact of Commodities: Structural Change or Status quo in Sub-Saharan Africa? - (:unkn) unknown (My University, 2013)
Sub-Saharan African economies have been exposed to major global changes, in particular a long cycle of increase in commodity prices since the early-2000s, the growth of emerging countries, which are key drivers of high commodity prices and have become significant trade and investment partners, and since 2008, recession in their traditional export markets. These changes may generate structural transformation, hence requiring a reconceptualisation of the integration of Sub-Saharan Africa into the world economy. China is a major trade partner and investor in commodities, industrial sectors and infrastructures in Sub-Saharan Africa. Will this trade and investment pattern preserve the status quo and entrenchment of market and export structures characterised by the pre-eminence of commodities? Or, in improving governments' fiscal space, will it foster opportunities for structural change? It is argued that it is the presence of 'developmental' political economies that, in the end, creates opportunities for diversification, industrialisation and structural transformation.
Keywords: African Research